Woman Searching for Family Nafkah in Islamic Economic Views - Nurhadi Nurhadi (AL-TAHRIR, 2019)
Abstract: This article focuses on the discussion of Islamic and economic views on women making a living for families (husbands and children). This phenomenon is already popular in Indonesian society, with many female workers (TKW) making a living or working abroad for the sake of family survival (husband and children), this is also reinforced by soap opera shows on private national television titled “The world is upside down” as a manifestation of the socio-economic facts of the Indonesian family today which is visualized as soap operas. This is a big question mark for socio-economic observers and practitioners of sakinah or Muslim families. In general, the main task of making a family living in Islam is assigned to the man (husband). Although it is justified that women (wives) earn a living (working) to help the family economy if the husband’s income is insufficient for family needs, provided that the woman in work does not bring shame, slander and harm to herself and the continuity of her household, and can maintain her honor by always covering aurat and keep away from things that produce salaries are not halal (haram). So a woman who is a family breadwinner in the view of Islamic economics is permitted, but that as an alternative to maintaining survival and domestic life with her husband and children, also does not violate her nature as a wife and mother for her children. This analysis arises because economic activity is a social activity, so the social is very closely related to the economy, also the Islamic economy and  ocioeconomic family in Islam.